Sexual Health Education in OB-Gyn Residencies—The Program Directors' Survey. Issue 4 (2nd October 2018) - Worly, Brett; Manriquez, Maria; Stagg, Amy; Hsieh Blanchard, May; Ogburn, Tony; Carson, Sandra; Woodland, Mark B.
Abstract: Objective : To evaluate U.S. obstetrics-gynecology (OB-Gyn) program Director appraisal of resident physician female sexual health training. Methods : An OB-Gyn resident sexual health curriculum survey was developed and sent to 237 U.S. OB-Gyn program directors. University/military programs were compared to community-based programs. Results : 115 OB-Gyn residency program directors responded (48.5% participation); 37.9% university/military and 43.2% community OB-Gyn Program Directors appraise the resident curriculum as "not well" preparing residents to manage sexual health therapies upon graduation. Topics not sufficiently covered include human sex trafficking, sexual health for women with disabilities, and cultural competency. Conclusions : This study identifies opportunities in OB-Gyn residency female sexual health education.